Annona muricata L. and Annona squamosa L. (Annonaceae): A review of their traditional uses and anticancer activities - GNANGA, Mahunakpon NG; AGBOKPONTO, JANVIER ENGELBERT (My University, 2021)
Over the past century, research on cancer has increased due to the importance of the disease as sixth leading cause of mortality worldwide. Several medicines, methods and strategies have been used to cure the disease. However, the problematic of drug resistance faced by researchers and physicians before different cancer types remains a big challenge. Therefore, basic plant research has produced new bioactive compounds with promising prospects in this regard. Phytotherapy appears then as a potential alternative for the discovery of new drugs in the fight against cancer and its drug resistance.
Keywords: Annona muricata L.; Annona squamosa L.; bioactive compounds; anticancer activities